The Contribution of Locus of Control to Academic Procrastination in Islamic Education Management Students in Indonesia - Juliana Batubara (AT-TA'LIM, 2017)
This study aimed to describe the locus of control and academic procrastination, and investigate whether there is significance contributions of locus of control on student academic procrastination. This research was conducted by the Ex post-facto method was used in this study, where the data taken from two set of questionnaires. Proportional Stratified Random Sampling was used. There were 107 students involved this study. The results showed that the locus of control is in average level, meanwhile, and the students’ academic achievement was high. The study also showed that there is a significant contribution between the locus of control on students' academic procrastination. The article concludes that the importance that locus control for procrastination research, and with suggestions for educators who work with students who are adversely affected by procrastination.